The impact of creatine supplementation on the development of kidney disease – literature review - Matczak, Mateusz; Jasiński, Karol; Broda, Aleksandra; Hoksa, Kacper; Jodłowski, Krzysztof; Dubniewicz, Ewa; Majewska, Paula; Staszek, Alicja; Łoskot, Wiktoria; Szwech, Jan (Quality in Sport, 2025)
Introduction: Creatine, a widely studied dietary supplement, is known for enhancing athletic performance and muscle strength. Concerns persist regarding its impact on kidney health, as it raises serum creatinine levels, potentially confounding renal function assessments. This review examines creatine’s role in sports and clinical contexts, emphasizing safety and kidney health implications. Aim of the study: To assess the effects of creatine supplementation on kidney function by summarizing evidence from case studies, clinical trials, and long-term research, addressing safety concerns in healthy and at-risk individuals. State of knowledge: Research supports creatine’s efficacy in improving athletic performance, recovery, and muscle strength, with therapeutic benefits in neurodegenerative diseases, type 2 diabetes, aging, and chronic conditions. Robust trials show no adverse renal effects in healthy individuals, even with long-term or high-dose use. However, case reports highlight potential risks for individuals with pre-existing kidney conditions, especially without monitoring. Elevated serum creatinine levels caused by creatine can mislead eGFR-based renal function tests, warranting cautious interpretation. Conclusions: When used as recommended, creatine is safe and effective for improving athletic and clinical outcomes in healthy individuals. While no direct renal impairment has been observed, caution is essential for those with kidney conditions. Pre-supplementation renal assessments, individualized dosing, and regular monitoring are advised to minimize risks. Creatine remains a valuable supplement, and further research is needed to confirm its long-term safety across various populations.